The Problem That Is not There: On the Old and New Interpretations of the Tent-Like Churches in Russian Architecture - Ivan Sablin (Anastasis: Research in Medieval Culture and Art, 2019)
The article deals with the long-discussed problem of the so-called tent-like churches in Russian architecture (of the XVI to the XVII centuries), with all existing theories of their origin being considered, presenting two opposed views tentatively termed the isolationist and the internationalist ones, not excluding those, who tried to go away from this strict opposition. An attempt at the radical solution that rejects a traditionally accepted notion of this type’s originality and uniqueness is made, with a proposal to take it instead for quite an ordinary variation of the eight-sided cloister vaults wide-spread in medieval architecture, that at times could be turned into these tents by simply straightening their otherwise curved constructions thus creating some kind of a pyramid. If properly investigated with all necessary parallels in Western architecture taken into account, even a search for the deeper symbolic meaning of this construction type (be that a holy place for the civil power representative or an allusion to St. Sepulchre) may become dispensable; this approach permits to treat instead the phenomenon as an incidental one caused by the mere formal and technical experiments and to a certain extent explicable by the intrusion of the Italian architects in the medieval Grand Duchy of Moscow.